2010
DOI: 10.1093/ntr/ntq083
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and initial smoking lapses among heavy drinkers in smoking cessation treatment

Abstract: Results suggest that alcohol-related lapses are qualitatively different from lapses that do not involve alcohol. Furthermore, among heavy drinkers in cessation treatment, even moderate alcohol use is associated with increased risk of smoking, with heavy drinking further increasing the risk. Smoking cessation treatments for heavy alcohol drinkers should highlight the lapse risk associated with any alcohol consumption and with heavy drinking during a quit smoking attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 27 publications
7
96
1
Order By: Relevance
“…Attempts to quit smoking are less successful among those with alcohol use disorder 13, 14, 15 and episodes of alcohol consumption during a smoking cessation attempt are associated with a greater risk of relapse to smoking 16. Several mechanisms may contribute to the association between alcohol and tobacco use, including genes involved in regulating neurotransmitters, cross‐tolerance and cross‐sensitization to both drugs, conditioning mechanisms in which cravings for alcohol or nicotine are elicited by similar environmental cues, and common psychological and social factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to quit smoking are less successful among those with alcohol use disorder 13, 14, 15 and episodes of alcohol consumption during a smoking cessation attempt are associated with a greater risk of relapse to smoking 16. Several mechanisms may contribute to the association between alcohol and tobacco use, including genes involved in regulating neurotransmitters, cross‐tolerance and cross‐sensitization to both drugs, conditioning mechanisms in which cravings for alcohol or nicotine are elicited by similar environmental cues, and common psychological and social factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is common for smokers to be advised to restrict their alcohol consumption when they are attempting to stop smoking 16, 25, 26. Survey data suggest that many smokers follow this advice, with increased rates of attempts to reduce alcohol consumption and less frequent binge drinking among those having recently begun an attempt to quit smoking 27.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, almost all unaided quitters (95%) resume regular smoking (Hughes, Keely, & Naud, 2006), and relapse is frequently preceded by isolated incidents of cigarette smoking known as lapses (Kenford et al, 1994). Three specific high-risk triggers-alcohol consumption (Brandon, Tiffany, Obremski, & Baker, 1990;Kahler, Spillane, & Metrik, 2010;Leeman et al, 2008;Shiffman, Paty, Gnys, Kassel, & Hickcox, 1996b;van Zundert, Kuntsche, & Engels, 2012), presence of others smoking (Shiffman, 1982;Shiffman et al, 1996b;Solomon et al, 2007), and negative affect (Kenford et al, 2002;Niaura et al, 2001;Shiffman et al, 1996b)-have consistently been identified as critical postcessation precipitants of lapse/relapse. However, exceedingly few data have addressed how these triggers combine to impact cessation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers attempting to quit report higher craving for cigarettes (Delfino, Jamner, & Whalen, 2001;Piasecki, McCarthy, Fiore, & Baker, 2008;Piasecki et al, 2011) and are significantly more likely to lapse after they consume alcohol (Brandon et al, 1990;Kahler et al, 2010;Leeman et al, 2008;Shiffman et al, 1996b;van Zundert et al, 2012). Furthermore, smokers who drink more after they quit smoking are significantly less likely than those who drink less to maintain long-term smoking abstinence (Hyland et al, 2004;McClure, Wetter, deMoor, Cinciripini, & Gritz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Our explanation for this finding revolves around social contexts for smoking and barriers to cessation. Alcohol consumption has previously been shown to be strongly related to increased risk of smoking relapse among quitters who are heavy drinkers (Kahler, Spillane, & Metrik, 2010;McKee, Krishnan-Sarin, Shi, Mase, & O'Malley, 2006), and this may be particularly true for men (Westmaas & Langsam, 2005). Further, heavier, more problematic drinkers are substantially more likely to drink in bars than those who consume less alcohol and drink less problematically (Single & Wortley, 1993), and smoking often accompanies this drinking.…”
Section: Discussionmentioning
confidence: 97%